Is Informality Welfare-Enhancing Structural Transformation? Evidence from Uganda - Fox, Louise; Pimhidzai, Obert (2012)
While Africa's recent decade of growth and poverty reduction performance has been lauded, concern has been expressed regarding the structure of this growth. In particular, questions have been raised about whether the growth is based on a commodities boom, or whether it is the beginning of a structural transformation that will lift workers from low-productivity jobs into higher-productivity ones. Macro evidence has suggested that the structural transformation has not started. But macro analysis misses the evidence that the process of transformation has started, because this process begins at the household level. Household livelihoods do not move from ones based on subsistence farming and household level economic activities into livelihoods based on individual wage and salary employment away from the household in one leap -- this process takes generations. The intermediate step is the productive informal sector. It is income gains at the household level in this sector that fuel productivity increases, savings, and investment in human capital in this sector. Ensuring that most households are able to diversify their livelihoods into the non-farm sector through productive informality not only increases growth, but also allows the majority of the population to share in the growth process. This paper illustrates this point with the case of Uganda which followed this path and experienced two decades of sustained growth and poverty reduction.